Engineering salt-tolerant Cas12f1 variants for gene-editing applications - Daskalakis, Vangelis; Papapetros, Spyridon (My University, 2023)
CRISPR has revolutionized the field of genome editing in life sciences by serving as a versatile and state-of-the-art tool. Cas12f1 is a small nuclease of the bacterial immunity CRISPR system with an ideal size for cellular delivery, in contrast to CRISPR-associated (Cas) proteins like Cas9 or Cas12. However, Cas12f1 works best at low salt concentrations. In this study, we find that the plasticity of certain Cas12f1 regions (K196-Y202 and I452-L515) is negatively affected by increased salt concentrations. On this line, key protein domains (REC1, WED, Nuc, lid) that are involved in the DNA-target recognition and the activation of the catalytic RuvC domain are in turn also affected. We suggest that salt concentration should be taken in to consideration for activity assessments of Cas engineered variants, especially if the mutations are on the protospacer adjacent motif interacting domain. The results can be exploited for the engineering of Cas variants and the assessment of their activity at varying salt concentrations. We propose that the K198Q mutation can restore at great degree the compromised plasticity and could potentially lead to salt-tolerant Cas12f1 variants. The methodology can be also employed for the study of biomolecules in terms of their salinity tolerance.Communicated by Ramaswamy H. Sarma.
Keywords: Cas12f; biomolecular engineering; crispr-cas; machine learning; protein thermostability